Agmatine’s Antidepressant-like Effect in Mice: Possible Contribution of N-Methyl-D-Aspartate (NMDA) Receptors and L-Arginine-Nitric Oxide Pathway - Abdulrahman M. Alahdal; Atef A. Al-Essawy; Amen M. Almohammadi (Journal of King Abdulaziz University: Medical Sciences, 2023)
In a mammalian brain, agmatine is an endogenous neurotransmitter and/or neuromodulator which is considered an endogenous ligand for ?2-adrenergic and imidazoline receptors. It blocks N-methyl-Daspartate subtype of glutamate receptors and inhibits all isoforms of nitric oxide synthases. Both, N-methyl-D-aspartate receptors and nitric oxide system have been implicated in the regulation of various behavioral, cognitive and emotional processes e.g. learning, aggression, locomotion, anxiety and depression. This study aimed at investigating the antidepressant-like effect of agmatine and the possible participation of Nmethyl- D-aspartate receptors and L-arginine-nitric oxide pathway in this effect. Agmatine (1, 10, 50 mg/kg, i.p.) possessed an antidepressant-like effect in two experimental models of depression; the forced swimming test and the tail suspension test in mice. Agmatine significantly enhanced the anti-immobility effect of imipramine, but did not affect that of ketamine (noncompetitive N-methyl-D-aspartate antagonist). The anti-immobility effect of agmatine assessed in the forced swimming test was completely prevented by pretreatment of mice with ascorbic acid (neuromodulator that antagonizes N-methyl-D-aspartate) or L-arginine (nitric oxide precursor). Agmatine elicited a significant antidepressant-like effect through an interaction with N-methyl-D-aspartate receptors and L-arginine-nitric oxide pathway. A possible synergism between imipramine and agmatine has been detected which may be useful clinically.